La acción tutorial y el rendimiento académico en los estudiantes de 8vo de la Unidad Educativa del Milenio Lcda. Olga Campoverde del cantón Huaquillas, durante el periodo lectivo 2023-2024 - Cárdenas Ruiz, Norma Maritza (2023)
Tutoring is an educational process in which a tutor provides guidance and personalized support to a student to improve his or her learning and academic development. The objective of this research was to analyze the tutorial action in the teaching-learning process and to determine the factors that affect the academic performance of 8th EGB students of the Milenio Educational Institution with Prof. Olga Campoverde of Huaquillas canton during the period 2023-2024. We worked with a mixed approach, framed in a non-experimental design, its descriptive scope, as well as the scientific, deductive, and analytical methods, which were necessary for the development of the research, the sample corresponds to 30 8th-grade students whose report cards were used to determine the academic performance where it was obtained as an important result that 22% of the population does not reach the required learning, therefore a proposal was designed based on activities aimed at improving the tutorial action and thus achieve a positive impact on the academic performance of students. In conclusion, this research highlights tutorial action as a valuable resource for optimizing academic performance in 8th-grade students. The results suggest that effective tutoring goes beyond the transmission of knowledge, involving socio-emotional aspects and adapting pedagogical strategies to meet the individual needs of students. The contributions of this study can influence pedagogical and strategic decision-making, thus improving the educational system. Keywords: Tutorial action, socioemotional approach, pedagogical strategies, academic performance, knowledge transmission.